Pathogenicity study of local bluetongue virus isolates in local and imported sheep - Sendow, Indrawati (Indonesian Journal of Animal and Veterinary Sciences, 2005)
Bluetongue is one of arboviruses that caused economical impact to sheep farmers. Six local bluetongue virus (BT) serotypes isolates were obtained from sentinel cattle blood in West Java and Irian Jaya (Papua), but its pathogenicity has not been identified. Propagation of viraemic blood inoculum from 3 local BT serotypes such as serotypes 1,9 and 21, that had been conducted in Merino sheep, will be used for pathogenicity study. The study was devided into 3 groups, each group contained local and imported sheep as control and infected sheep. All sheep had been tested as negative BT antibodies. Observation on clinical signs had been conducted twice daily for 28 days. Heparinised blood and sera were collected everyday to obtain the viraemia period by Ag-C-ELISA test and antibody respons by C-ELISA test. The clinical signs produced were varied from normal to very mild in local sheep and very mild to mild-moderate in Merino sheep.The lowest severe degree of clinical signs was BT 9 followed by BT 1 and BT 21. No dead, neither local and Merino sheep occurred. Viraemia in Merino sheep occurred between 3-5 days and in local sheep between 4-7 days post inoculation (DPI). Antibody respons occurred as quick as 10 DPI in Merino sheep and 9 DPI in local sheep, and stayed until the end of experiment. This study showed that local BT isolates were not pathogen and not producing clasical BT infection. Â  Â  Key Words: Bluetongue Virus, Antibody Respons, Viraemia, Serology, Sheep